Tuning the Synthetic Routes of Dimethylaminoethyl methacrylate‐Based Superabsorbent Copolymer Hydrogels Containing Sulfonate Groups: Elasticity, Dynamic, and Equilibrium Swelling Properties - Boyaci, Talin; Orakdogen, Nermin (Wiley, 2015)
ABSTRACTSuperabsorbent copolymer hydrogels based on N,N‐dimethylaminoethyl methacrylate (DMAEMA) and 2‐acrylamido‐2‐methylpropane sulfonic acid (AMPS) were synthesized by free‐radical cross‐linking copolymerization using a bifunctional cross‐linking agent diethylene glycol dimethacrylate (DEGDMA). Poly(DMAEMA‐co‐AMPS) (P(DMAEMA‐co‐AMPS)) hydrogels were prepared at a fixed cross‐linker ratio, but at various ionic comonomer AMPS content between 0 and 50 mol%. The effect of ionic comonomer concentration on the equilibrium swelling, mechanical behavior, and swelling–deswelling kinetics was investigated to find materials with satisfactory swelling and elastic properties. The increase in the ionic comonomer AMPS content increased the equilibrium swelling of copolymer hydrogels. Using the Flory–Rehner theory, the equilibrium swelling behavior of P(DMAEMA‐co‐AMPS) hydrogels was successfully investigated and the effective charge density of the resulting copolymer hydrogels was calculated as an adjustable parameter. Scaling rules were derived for the ionic group content to explain the observed swelling behavior of P(DMAEMA‐co‐AMPS) hydrogels. The kinetics of copolymer hydrogel swelling as well as the mechanism of diffusion was investigated by dynamic swelling measurements at different pH values. The dominant physical mechanism controlling the water uptake of P(DMAEMA‐co‐AMPS) copolymer hydrogels was analyzed, and the diffusion coefficients were determined. The transport was found to be less Fickian for the copolymer hydrogels containing AMPS below 30 mol% at acidic pH values where the polymer networks were ionized.